PENGARUH SLACK RESOURCES, GENDER, DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - made sudarma; Putu Prima Wulandari; Steffi Lituhayu Van Tama; Made Tara Damayanti (KRISNA: Kumpulan Riset Akuntansi, 2023)
The study aims to determine the effect of slack resources, gender, and ownership structure on company value of companies listed on the IDX during the 2021-2022, as 660 sample during the period and 154 samples were taken according to criteria. The research approach used in this study is quantitative research. The utilized data analysis model in this study was multiple linear regression analysis. The results show that the variables of financial slack, organizational slack, innovation slack, gender of the board of directors, gender of the board of commissioners have no effect on firm value. Meanwhile, managerial ownership variables, as well as institutional ownership have an effect on firm value.